Association of human papillomavirus integration with better patient outcomes in oropharyngeal squamous cell carcinoma. Issue 2 (19th October 2020) - Pinatti, Lisa M.; Sinha, Hana N.; Brummel, Collin V.; Goudsmit, Christine M.; Geddes, Timothy J.; Wilson, George D.; Akervall, Jan A.; Brenner, Chad J.; Walline, Heather M.; Carey, Thomas E.
Abstract: Background: The molecular drivers of human papillomavirus‐related head and neck squamous cell carcinoma (HPV + HNSCC) are not entirely understood. This study evaluated the relationship between HPV integration, expression of E6/E7, and patient outcomes in p16+ HNSCCs. Methods: HPV type was determined by HPV PCR‐MassArray, and integration was called using detection of integrated papillomavirus sequences polymerase chain reaction (PCR). We investigated whether fusion transcripts were produced by reverse transcriptase polymerase chain reaction (RT‐PCR). E6/E7 expression was assessed by quantitative RT‐PCR. We assessed if there was a relationship between integration and E6/E7 expression, clinical variables, or patient outcomes. Results: Most samples demonstrated HPV integration, which sometimes resulted in a fusion transcript. HPV integration was positively correlated with age at diagnosis and E6/E7 expression. There was a significant difference in survival between patients with vs without integration. Conclusions: Contrary to previous reports, HPV integration was associated with improved patient survival. Therefore, HPV integration may act as a molecular marker of good prognosis.